Coherent Structural and Functional Network Changes after Thalamic Lesions in Essential Tremor. Issue 9 (23rd June 2022) - Pohl, Emily D.R.; Upadhyay, Neeraj; Kobeleva, Xenia; Purrer, Veronika; Maurer, Angelika; Keil, Vera C.; Kindler, Christine; Borger, Valeri; Pieper, Claus C.; Groetz, Simon; Scheef, Lukas; Maciaczyk, Jaroslaw; et al.
Abstract: Background: Magnetic resonance–guided focused ultrasound of the ventral intermediate nucleus is a novel incisionless ablative treatment for essential tremor (ET). Objective: The aim was to study the structural and functional network changes induced by unilateral sonication of the ventral intermediate nucleus in ET. Methods: Fifteen essential tremor patients (66.2 ± 15.4 years) underwent probabilistic tractography and functional magnetic resonance imaging (MRI) during unilateral postural tremor‐eliciting tasks using 3‐T MRI before, 1 month (N = 15), and 6 months (N = 10) post unilateral sonication. Results: Tractography identified tract‐specific alterations within the dentato‐thalamo‐cortical tract (DTCT) affected by the unilateral lesion after sonication. Relative to the treated hand, task‐evoked activation was significantly reduced in contralateral primary sensorimotor cortex and ipsilateral cerebellar lobules IV/V and VI, and vermis. Dynamic causal modeling revealed a significant decrease in excitatory drive from the cerebellum to the contralateral sensorimotor cortex. Conclusions: Thalamic lesions induced by sonication induce specific functional network changes within the DTCT, notably reducing excitatory input to ipsilateral sensorimotor cortex in ET. ©[2022] International Parkinson and Movement Disorder Society. © 2022 The Authors. Movement Disorders published by Wiley Periodicals LLC on behalf of International Parkinson and Movement Disorder Society